2022
DOI: 10.1007/s43684-022-00022-6
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Decision making in circular economy using generalized colored stochastic Petri nets

Abstract: Circular economy enables to restore product value at the end of life i.e. when no longer used or damaged. Thus, the product life cycle is extended and this economy permits to reduce waste increase and resources rarefaction. There are several revaluation options (reuse, remanufacturing, recycling, …). So, decision makers need to assess these options to determine which is the best decision. Thus, we will present a study about an End-Of-Life (EoL) decision making which aims to facilitate the industrialization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Several types of methods have been developed to support end-of-life phase decision-making. Vanson et al (2022) distinguish between end-of-life assessments, disassembly assessments and other assessment methods. They showed that mathematical models, multi-criteria analyses (MCAs) and cost-benefit analyses are the most common types of methods within these categories.…”
Section: Demolition Waste Management Decision-making Methodsmentioning
confidence: 99%
“…Several types of methods have been developed to support end-of-life phase decision-making. Vanson et al (2022) distinguish between end-of-life assessments, disassembly assessments and other assessment methods. They showed that mathematical models, multi-criteria analyses (MCAs) and cost-benefit analyses are the most common types of methods within these categories.…”
Section: Demolition Waste Management Decision-making Methodsmentioning
confidence: 99%
“…Techniques upon which CE can be performed include reuse, remanufacturing, recycling, etc. (Vanson et al, 2022). For CE to be effectively implemented, a conscious effort must be made in regulatory legislation, governmental policy, administrative model, product design model, supply chain management, and waste management (Smol et al, 2020;Kazancoglu et al, 2021).…”
Section: Circularity In Municipal Solid Waste Managementmentioning
confidence: 99%